Choice a criteria for estimating the electromagnetic compatibility of tractive converters of perspective electric locomotive - Bondarenko, Yu. S. (Science and Transport Progress, 2012)
The article is devoted to the justification and the choice among existing criteria for determining the electromagnetic compatibility of high-frequency static converter, which is part of the modern electric rolling stock systems, with the systems of electric railways.